Business cycle and spillover effects on pre-retirement behavior in Spain - Sergi Jimenez-Martin; Judit Castello (IZA Journal of European Labor Studies, 2013)
We test the hypothesis that exits from the labor market for pre-retirement individuals in Spain respond mainly to economic conditions and to incentives by analyzing two effects. First, we test the existence of spillover effects from a reform of the old-age pension system on transitions from employment to disability, unemployment and inactivity. We exploit the fact that the reform only affected individuals that had contributed between 15 and 25 years to the Social Security. Second, we estimate the effect of business cycle (BC) conditions at the local, sector and national level on these transitions. We find that both factors affect the exit timing and the choice of route out of the labor market.
Keywords: J21; J22; R23; 330; Spillover effects; Business cycle conditions; Disability benefits